Shaping the human brain: evolutionary cis-regulatory plasticity drives changes in synaptic activity-controlled adaptive gene expression - Pruunsild, Priit; Bading, Hilmar (Current opinion in neurobiology, 2019)
Neuronal activity-induced gene expression programs involved in synaptic structure- and plasticity-related functions are similar in mice and humans, yet bear distinct features. These include gains or losses of activity-responsiveness of certain genes and differences in gene induction profiles. Here, we discuss a possible origin of dissimilarities in activity-regulated transcription between species. We highlight that while synapse-to-nucleus signalling pathways are evolutionarily conserved, cis-regulatory plasticity has been driving species-specific remodelling of the activity-controlled enhancer landscape, thereby affecting gene regulation. In particular, evolutionary rearrangements of transcription factor binding site placements together with potential species-dependent developmental stage- and/or cell type-specific epigenetic and other trans-acting mechanisms are most likely at least in part accountable for between-species diversity in activity-regulated transcription. It is conceivable that cis-regulatory plasticity may have equipped the synaptic activity-driven adaptive gene program in human neurons with unique, species-specific qualities.
Gesehen am 21.01.2020